Transformations of public gatherings into civil disorder in pandemic-driven Sweden and Finland - Skrzypek, Maciej (Palgrave Macmillan, 2024)
This paper investigates the dynamics behind the escalation of peaceful public gatherings into civil disorder in Finland and Sweden, both of which have high levels of public trust in governance. The study focuses on how protest policing and police partisanship influence the transformation of collective action into civil disorder. The research questions are as follows: What factors occurred in the case of transformation, and what are the dynamics of civil disorder in these contexts? The study employs process tracing and crisp-set variant of qualitative comparative analysis to analyze data from ACLED on protests in Helsinki and Stockholm from March 2020 to March 2022. The paper delivers an understanding of the dynamics of civil disorder at public gatherings in pandemic-ridden democratic states. The findings offer insights into how pandemic-related restrictions influenced protester behavior and provide guidance for maintaining public order while respecting the right to protest in crisis situations.
Keywords: civil disorder; Finland; Sweden; coronavirus; public gatherings